Translation of Continuous Function Charts to Imperative Synchronous Quartz Programs - Werner, Marcel Christian; Schneider, Klaus (2021 19th ACM-IEEE International Conference on Formal Methods and Models for System Design (MEMOCODE), 2021)
Programmable logic controllers operating in a sequential execution scheme are widely used for various applications in industrial environments with real-time requirements. The graphical programming languages described in the third part of IEC 61131 are often intended to perform open and closed loop control tasks. Continuous Function Charts (CFCs) represent an additional language accepted in practice which can be interpreted as an extension of IEC 61131-3 Function Block Diagrams. Those charts allow more flexible positioning and interconnection of function blocks, but can quickly become difficult to manage. Furthermore, the sequential execution order forces a sequential processing of possible independent and thus possibly parallel program paths. The question arises whether a translation of existing CFCs to synchronous programs considering independent actions can lead to a more manageable software model. While current formalization approaches for CFCs primarily focus on verification, the focus of this approach is on restructuring and possible reuse in engineering. This paper introduces a possible automated translation of CFCs to imperative synchronous Quartz programs and outlines the potential for reducing the states of equivalent extended finite state machines through restructuring.